The Effect of Compensation and Perceived Organizational Support on the Performance of Maxim Drivers - Chandra, Felix (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines how compensation systems and organizational support influence the performance of Maxim driver-partners who operate in Ambon City. The research employed a quantitative survey method with 35 respondents selected through purposive sampling. Data were collected using a 5-point Likert scale questionnaire and analyzed using multiple regression after ensuring instrument validity and model feasibility. The findings indicate a significant positive relationship between compensation levels and driver performance. Similarly, drivers’ perceived organizational support was found to positively affect their performance quality. When combined, these two factors significantly enhance performance, suggesting that optimal outcomes can be achieved through adequate compensation policies accompanied by continuous organizational support. The results of this study provide strategic insights for Maxim management to refine compensation policies and strengthen support systems for driver-partners in order to maintain service standards and improve driver welfare.